Career Paths and Socio-Economic Status - Riverin-Simard, Danielle (Canadian Journal of Counselling and Psychotherapy, 2009)
Few of the sequential models of adult vocational development have undertaken a comparative identification of career paths according to the socio-economic status of workers. On the basis of interviews carried out with 786 adults, randomly assigned after stratifying according to three socio-economic classes, nine age strata, two genders and three working sectors, this article presents three vocational trajectories within the three social classes, each comprising nine phases of working life. The integrative model has been elaborated on the basis of these results. This article proposes two of its main principles: 1) equilibrated integration of adaptive and creative functions; 2) vocational continuitv within time-spaces.